A randomised controlled trial on effect of topical anaesthetics on injection pain during immunization in infants of 6 weeks to 6 months of age with pentavac vaccine - D. K., Sowmiya; R., Ramanathan; R., Ramamoorthy (International Journal of Contemporary Pediatrics, 2023)
Background: Pain is a both a sensory and an emotional experience when untreated and unrecognized, it extracts a significant physiological, biochemical and psychological toll on both the children and family members. Vaccine injections are considered to be the most common cause of iatrogenic pain in childhood. Positive experience during vaccine injection like reducing injection pain with local anaesthetics can avoid pre procedural anxiety in future, needle phobias, healthcare avoidance behaviors and maintain trust in healthcare providers. Methods: This randomized controlled trial was done at immunization clinic of Rajah Muthiah Medical College Hospital over a period of 2 years.100 infants of age group 6 weeks to 6 months brought for Pentavac (DPT-Hib-Hepatitis B) combination vaccine were taken for study and allocated into control, intervention group (receiving local anaesthetic cream/lidocaine spray) and pain score was compared using modified behavioral pain score (MBPS). Results: Among the three groups studied, the mean pain scores after vaccine injection were minimum in group A (infants with topical occlusive EMLA cream), followed by group B (infants with topical LA spray), whereas control group of infants who did not receive any local anaesthesia exhibited higher pain scores values. Conclusions: Our study showing that topical occlusive EMLA cream significantly decreases injection pain in infants has applicability in clinical practice, where it can be routinely used in infants before administering intramuscular vaccine injections in settings where resources are not a constraint.